Structural evolution of liquid silicates under conditions in Super-Earth interiors - Guillaume Morard; Jean-Alexis Hernandez; Clara Pege; Charlotte Nagy; Lélia Libon; Antoine Lacquement; Dimosthenis Sokaras; Hae Ja Lee; Eric Galtier; Philip Heimann; Eric Cunningham; Siegfried H. Glenzer; et al. (Nature Communications, 2024)
Abstract Molten silicates at depth are crucial for planetary evolution, yet their local structure and physical properties under extreme conditions remain elusive due to experimental challenges. In this study, we utilize in situ X-ray diffraction (XRD) at the Matter in Extreme Conditions (MEC) end-station of the Linear Coherent Linac Source (LCLS) at SLAC National Accelerator Laboratory to investigate liquid silicates. Using an ultrabright X-ray source and a high-power optical laser, we probed the local atomic arrangement of shock-compressed liquid (Mg,Fe)SiO3 with varying Fe content, at pressures from 81(9) to 385(40) GPa. We compared these findings to ab initio molecular dynamics simulations under similar conditions. Results indicate continuous densification of the O-O and Mg-Si networks beyond Earth’s interior pressure range, potentially altering melt properties at extreme conditions. This could have significant implications for early planetary evolution, leading to notable differences in differentiation processes between smaller rocky planets, such as Earth and Venus, and super-Earths, which are exoplanets with masses nearly three times that of Earth.